Conflitos na aplicação de precedentes dos Tribunais Superiores em matéria tributária - Figueiredo, Marina Vieira de (2016)
The legal standards must not be confused with the prescriptive texts. The first are built from such texts, which allow different interpretations and the creation of conflicting rules. Therefore, the conflict between standards is an embedded problem in the legal system. Among the conflicts which are relevant, those verified among standards derived from a single precedent of the Superior Courts stand out. Current legislation confers special attention to decisions issued by these bodies, imposing their applicability to similar cases. There is no point, however, in granting a binding effect to the precedents if there is no uniformity in their application. It is true, however, that the commonly chosen criteria for rule conflict resolution are not enough to solve this kind of contradiction, since the rules derived from the same precedent: (i) hold the same hierarchy; (ii) are equally general; and (iii) are contemporaneous. This, however, does not mean that there are no criteria liable to resolve such antinomies. Analyzing our legal system, we see that any act of implementing rules (judicial decision there included) always has the same configuration: the norm is created for means of specific concrete application, there is an assessment in order to identify if the facts are comprised by what the aforementioned legal standards set forth, and only then a legal relationship between certain individuals is constituted. Therefore, the construction of a rule based on a precedent will, necessarily, observe these aspects: applicable provision, facts taken into consideration upon decision issuance and how the dispute was settled. The latter, in its turn, will be the first step towards the resolution of conflicts upon its application. Once the ratio decidendi, i.e. the rule of the precedent, is determined then it is time to check whether the jurisdiction for which it provides (power to apply the precedent for similar cases) was legally exerted. If an illegality is identified – resulting from a controversial precedent interpretation – this allows for the application of the penalty provided in the standard of competence: invalidity declaration of the illegally created standard